Age-related deficits in selective attention during encoding increase demands on episodic reconstruction during context retrieval: An ERP study. (June 2016) - James, Taylor; Strunk, Jonathan; Arndt, Jason; Duarte, Audrey
Abstract: Previous event-related potential (ERP) and neuroimaging evidence suggests that directing attention toward single item-context associations compared to intra-item features at encoding improves context memory performance and reduces demands on strategic retrieval operations in young and older adults. In everyday situations, however, there are multiple event features competing for our attention. It is not currently known how selectively attending to one contextual feature while attempting to ignore another influences context memory performance and the processes that support successful retrieval in the young and old. We investigated this issue in the current ERP study. Young and older participants studied pictures of objects in the presence of two contextual features: a color and a scene, and their attention was directed to the object's relationship with one of those contexts. Participants made context memory decisions for both attended and unattended contexts and rated their confidence in those decisions. Behavioral results showed that while both groups were generally successful in applying selective attention during context encoding, older adults were less confident in their context memory decisions for attended features and showed greater dependence in context memory accuracy for attended and unattended contextual features (i.e., hyper-binding). ERP results were largely consistent between age groups but older adults showed a more pronounced late posterior negativity (LPN) implicated in episodic reconstruction processes. We conclude that age-related suppression deficits during encoding result in reduced selectivity in context memory, thereby increasing subsequent demands on episodic reconstruction processes when sought after details are not readily retrieved. Highlights: We measure the effect of selective attention at encoding on source memory retrieval. Age-related suppression deficits lead to hyper-binding in source accuracy. Older adults show enhanced late posterior negativity (LPN) ERPs during retrieval. Suppression deficits increase demands on post-retrieval reconstruction processes. Older adults' source memory ability may be especially impaired in noisy situations.